The Motion Verbs with Particles and Prepositions: Semantic Analyses - Haris Budiana (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2018)
Abstract The topic of this research figures out the features of the motion verbs with particles and prepositions. The objectives of the research are to describe the meanings of the motion verbs in verb-particle combinations, the specific meaning of the adverb and the prepositions in the concept of motions, The data are taken from three novels. The selection of the data is focused on the verbs which express the agentive manner of motion and which combine with adverbs or prepositions that follow. The motion verbs semantically express the agent’s moving from one place to another. The concept of motion event is represented by the moving figure, motion event, path, and ground. However, the case of the motion verbs with the particles and prepositions show the different sense of motion. There are two categories of meanings indicated by the verb-particle combinations namely literal and idiomatic. The idiomatic meanings of the motion are mostly derived from metaphors.  In the concept of motion event, the paths which are occupied by adverb or preposition or the combination of both contribute to the idiomatic meaning of the verbs.